Pengaruh Mata Kuliah Kewirausahaan Terhadap Minat Berwirausaha Pada Program Berwirausaha Pada Mahasiswa Program Studi Pendidikan Anak Usia Dini - Fitria Nur Afni Siregar; Dhinanda Aulia Fitri Parinduri; Emilia Fitri Harahap; Zahrawani Zahrawani; Mansur Keling (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Entrepreneurial interest is the desire, interest and willingness to work hard or the strong will to be independent or try to fulfill one's life needs without feeling afraid of the risks that will occur, as well as the willingness to learn from failure. This is the background for researchers to examine more deeply the influence of entrepreneurship courses on interest in entrepreneurship in entrepreneurship programs among students in the Early Childhood Education Study Program. This research uses a qualitative descriptive type of research with the research subjects being Early Childhood Education Students. Data collection tools include observation and interviews. The results of the research that we got were that program students were very interested in entrepreneurship when they finished their bachelor's degree because entrepreneurship in everyday life can be applied to early childhood teachers where when they teach at school they can do side jobs such as work online or sell online and then create entrepreneurial products that can increase their business.